Atomic Modulation, Structural Design, and Systematic Optimization for Efficient Electrochemical Nitrogen Reduction. Issue 4 (19th January 2020) - Huang, Yiyin; Babu, Dickson D.; Peng, Zhen; Wang, Yaobing
Abstract: Ammonia (NH3 ) is a pivotal precursor in fertilizer production and a potential energy carrier. Currently, ammonia production worldwide relies on the traditional Haber–Bosch process, which consumes massive energy and has a large carbon footprint. Recently, electrochemical dinitrogen reduction to ammonia under ambient conditions has attracted considerable interest owing to its advantages of flexibility and environmental friendliness. However, the biggest challenge in dinitrogen electroreduction, i.e., the low efficiency and selectivity caused by poor specificity of electrocatalysts/electrolytic systems, still needs to be overcome. Although substantial progress has been made in recent years, acquiring most available electrocatalysts still relies on low efficiency trial‐and‐error methods. It is thus imperative to establish some critical guiding principles for nitrogen electroreduction toward a rational design and accelerated development of this field. Herein, a basic understanding of dinitrogen electroreduction processes and the inherent relationships between adsorbates and catalysts from fundamental theory are described, followed by an outline of the crucial principles for designing efficient electrocatalysts/electrocatalytic systems derived from a systematic evaluation of the latest significant achievements. Finally, the future research directions and prospects of this field are given, with a special emphasis on the opportunities available by following the guiding principles. Abstract : Electrochemical dinitrogen reduction to ammonia is a promising technology, while the low efficiency and selectivity of electrocatalysts severely limit its applicability. Herein, a comprehensive picture of nitrogen reduction mechanism and guiding principles derived from atomic modulation, structural design, and systematic optimization studies are presented. The existing challenges and opportunities for advancing the development of electrochemical nitrogen reduction are also discussed.